Effect of Sowing Dates on the Bacterial Leaf Spot of Bottle Gourd and Pumpkin Caused by Xanthomonas cucurbitae - Sharma, Arpana; Jarial, Kumud; Jarial, R. S.; Sharma, Deepa (International Journal of Bio-resource and Stress Management, 2022)
An experiment was conducted at Experimental Farm, College of Horticulture and Forestry, Neri, Hamirpur during May 2019 to October, 2019 cropping season to study the effect of different sowing dates viz., 17th May (1st), 7th June (2nd), 27 June (3rd) and 17th July (4th) on the development of bacterial leaf spot of bottle gourd and pumpkin caused by Xanthomonas cucurbitae. It was observed that the mean disease severity in both bottle gourd and pumpkin crops decreased with delay in the date of sowing from mid May (40.15 and 31.73%, respectively) to the end of June (27th June, 31.65 and 27.06%, respectively) or mid July (17th July, 23.32 and 20.13%, respectively). The disease incidence was also found to be minimum in the fourth (31.31%) and third (39.60%) dates of sowing in case of bottle gourd fruits and no incidence of the bacterial spot was recorded in case of pumpkin fruits. In the case of bottle gourd, the expected yield loss was minimum in crops sown mid July (31.44%) while in pumpkin, the fruit yield was more in mid July (9.59 kg vine-1) sown crop in comparison to mid May and early June sown crops. So, it was concluded that late June and mid July sown crops of both bottle gourd and pumpkin are less vulnerable to the disease leading to reduced crop losses and higher yield.